Interaction between neuroticism and posttraumatic stress disorders of participants of the military actions - Kharchenko Дмитро; Chystovs’ka Юлія; Izvjekova Ольга (Psychosomatic Medicine and General Practice, 2018)
On the basis of complex analysis of psychophysiological properties, an attempt was made to find predictors of post-traumatic stress disorder. The revealed features of the interconnection of genetically determined properties of temperament with post-traumatic stress disorder in persons who were in the area of combat operations, namely between the level of neuroticism and the indicators of the clinical diagnostic criteria of CAPS, are reliable correlations. Consequently, individuals with a high level of neuroticism have a significantly higher probability of suffering from PTSD in extreme conditions.